An Employee engagement report - beyond the carrot and the stick : rethinking rewards & benefits in today's workplace - Bibko, Suzy (Osney Media LondonGB, 2010)
Examines how the concept of reward has changed from a narrow monetary concept of compensation, bonuses and benefits to the much broader "total reward" which includes components such as flexible benefits; access to professional and career development; freedom and autonomy at work; preferred office space; preferred office equipment and mobile phone; flexible working hours; working remotely.